Language component of the interethnic relations issues in the ethnically mixed regions along the Slovene-Hungarian border - Nećak Lük, Albina (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 1993)
In the article language related situations in two bilingual towns, in Lendava (Slovenia) and Monošter (Hungary) have been compared. The mother tongue and the second language proficiency and use by both the minority and the majority population have been analysed and the language attitudes have been investigated. In both environments the national adherence and the age of respondents appear to be the most relevant factors influencing the language related variables. The trend of diminished proficiency and use of the minoritylanguage with younger generations is quite evident in Monošter, and it can be noticed also in Lendava.
Keywords: dvojezičnost; etnični odnosi; jezikovne manjšine; Madžari; narodne manjšine; porabski Slovenci; Prekmurje; Slovenija; sociolingvistika